Pulled Polymer Loops as a Model for the Alignment of Meiotic Chromosomes - Lin, Yen Ting; Froemberg, Daniela; Huang, Wenwen; Delivani, Petrina; Chacon, Mariola; Tolic, Iva M.; Juelicher, Frank; Zaburdaev, Vasily (Physical Review Letters, 2015)
During recombination, the DNA of parents exchange their genetic information to give rise to a genetically unique offspring. For recombination to occur, homologous chromosomes need to find each other and align with high precision. Fission yeast solves this problem by folding chromosomes in loops and pulling them through the viscous nucleoplasm. We propose a theory of pulled polymer loops to quantify the effect of drag forces on the alignment of chromosomes. We introduce an external force field to the concept of a Brownian bridge and thus solve for the statistics of loop configurations in space.